2011
DOI: 10.1590/s1413-81232011000700056
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da qualidade da informação: linkage entre SIM e SINASC em Jaboatão dos Guararapes (PE)

Abstract: Evaluation of the quality of information: linkage between SIM and SINASC in Jaboatão dos Guararapes, Pernambuco State Guararapes (PE) Resumo O objetivo do presente estudo foi investigar a notificação da declaração de nascidos vivos (DNV) em residentes de Jaboatão dos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
0
7
0
7
Order By: Relevance
“…Infant mortality studies show that deaths during the neonatal period are more likely associated with genetic, pregnancy, type of delivery, and perinatal characteristics, while post-neonatal mortality is related to factors determined by living conditions and social characteristics, such as income, education, basic sanitation and treated clean water, and access to health services 8,12,14 . Neonatal mortality in Brazil accounts for more than 70% of mortality in the first year of life, with 25% of deaths occurring in the first 24 hours postpartum 17,18,19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infant mortality studies show that deaths during the neonatal period are more likely associated with genetic, pregnancy, type of delivery, and perinatal characteristics, while post-neonatal mortality is related to factors determined by living conditions and social characteristics, such as income, education, basic sanitation and treated clean water, and access to health services 8,12,14 . Neonatal mortality in Brazil accounts for more than 70% of mortality in the first year of life, with 25% of deaths occurring in the first 24 hours postpartum 17,18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…These data have been collected through information systems and epidemiologic studies, which are fundamental and of great relevance for the country. Specific limitations of information systems are related to sub-registries, particularly in regions with a historic lack of infant death information 4,10,11,12,13,14 . For example, in 2012 a Brazilian study actively searched for infant deaths in 79 small and medium size municipalities in the North and Northeast of the country, and found that public health monitoring coverage was below 80% in seven states 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altas estimativas de subnotificação são encontradas em vários estudos, de diferentes doenças e bancos de dados diversos 45,67,68,69,70,71,72 . Os trabalhos analisados na revisão integrativa supracitados apontam limitações e fragilidades que sugerem a ocorrência de subnotificações durante a pandemia 24 .…”
Section: Discussionunclassified
“…Tais informações são utilizadas na formulação e na avaliação de ações, planos e políticas de saúde, subsidiando o processo de tomada de decisões que podem contribuir e aprimorar a situação de saúde individual e coletiva 15 . Muitos estudos com metodologias distintas foram desenvolvidos no Brasil com o objetivo de qualificar e mensurar a confiabilidade das informações de mortalidade, bem como de outras bases de dados do Sistema Único de Saúde (SUS) 16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34 . 13 .…”
Section: Discussionunclassified